Effects of Demographic Characteristics and Consumer Behavior in the selection of Retail Pharmacies and Over-the-Counter Medicine - Kevrekidis D.P; Mináriková D.; Markos A. (Sciendo, 2022)
The study aimed to provide new insights into consumer behaviour by identifying the key demographic factors that influence the choice of pharmacy and over-the-counter (OTC) medicine.